THE LEISURE ETHOS IN THE MODERNISM AND POSTMODERNISM NOVEL (Proceedings of Southern Federal University. Philology, 2012)
Kotelevskaya V.V.Keywords: novel, modernism, postmodernism, narrative discours, ethos of the leisureThe article proposes to introduce a number of key modernist and postmodernist novels through specific social, cultural, and economic backgrounds. The question of leisure ethos assumes greater significance in light of the longing for the past in the new era of speed, production and consumption. The author traces the mutations of the novel in the twentieth century with reference to social and historical sources and sufficient reworking of the leisure idea by authors with very different beliefs and backgrounds (M. Proust, H. Hesse, F. Beigbeder, P. Handke, E. Jelinek, etc.).